Students’ Satisfaction toward the Services of the Chemical Laboratory - Lukum, Astin; Paramata, Yoseph (International Journal of Evaluation and Research in Education (IJERE), 2015)
Chemistry Laboratory serves all of the students that was programmed chemistry lab works. The satisfaction of the students was studied that involving 50 students, the study was conducted to measure the students' satisfaction towards the services offered by the laboratory, Measurement of the students' satisfaction was conducted using statistical parametric t-test. The study shows that the students' satisfaction more than 75%.Chemistry Laboratory serves all of the students that was programmed chemistry lab works. The satisfaction of the students was studied that involving 50 students, the study was conducted to measure the students' satisfaction towards the services offered by the laboratory, Measurement of the students' satisfaction was conducted using statistical parametric t-test. The study shows that the students' satisfaction more than 75%. <w:LsdException Locke